Pleural Mesothelioma Presenting as Periumbilical Metastasis: The First Clinical Documentation. (18th April 2013) - Falkenstern-Ge, R. F.; Kimmich, M.; Bode-Erdmann, S.; Friedel, G.; Ott, G.; Kohlhäufl, M.
Abstract : Introduction . Pleural mesothelioma with metastasis to the subcutaneous tissue of the abdominal wall at first diagnosis and without penetration into the peritoneum is an extremely rare clinical presentation. Methods . Patients with pleural mesothelioma have low survival rate. Usually, the disease at presentation is confined to its site of origin (most often the pleural cavity). A 55-year-old man was referred to our center due to increasing dyspnea and a painful periumbilical mass in the anterior abdominal wall. CT scan revealed both advanced mesothelioma of the pleura and a tumor mass confined to the subcutaneous fatty tissue without penetration through the peritoneum. Results . Video-assisted thoracoscopy confirmed the diagnosis of epithelioid pleural mesothelioma, which was also confirmed by a biopsy of the periumbilical mass. Systemic chemotherapy with cisplatin and pemetrexed was initiated. Under the ongoing systemic chemotherapy, the evaluation revealed partial remission of pleura mesothelioma and its subcutaneous manifestation of the abdominal wall. Conclusion . Mesothelioma of the pleura with a simultaneous metastasis to the subcutaneous fatty tissue of the abdominal wall at presentation without penetration of peritoneum is a rare clinical presentation of mesothelioma disease. The knowledge of its natural history is very limited. This is the first ever clinical documentation of a patient with pleura mesothelioma and simultaneous subcutaneous manifestation of abdominal wall.